Intercultural Synthesis of Ethnic Elements in Contemporary Vocal Practice: A Musicological Study with Statical Validation - Inesh Kdyrova; Alma Dossanova; Dilya Duiyessinova; Zhanar Shaikenova (Resital: Jurnal Seni Pertunjukan, 2025)
Contemporary vocal studies have not sufficiently developed quantitative models that combine the structural analysis of Eastern and Western musical elements with the measurement of their perception within a single analytical framework. Existing work mostly focuses either on describing stylistic characteristics or on cultural interpretations of hybridity, without offering formalized tools for comparing intonational, modal, and rhythmic parameters across traditions and assessing their impact on listening judgments. The purpose of the study was to empirically identify structural indicators of the synthesis of Eastern and Western vocal elements and to test their relationship with assessments of harmony, authenticity, and emotional expressiveness. For this purpose, a corpus of 200 vocal compositions from different regions was formed. The frequency of intonation, harmony, and rhythmic characteristics was recorded using automated spectral analysis in Sonic Visualizer. Groups were compared using Fisher's F-test and Student's t-test; additionally, standardized effect sizes (Cohen's d, η²) and 95% confidence intervals were calculated. The perceptual component of the study included 48 students in the vocal specialization who evaluated a selection of pieces on a 10-point scale according to three criteria: harmony of synthesis, preservation of authentic features, and emotional expressiveness. Harmony was operationalized as the average integral value of these three indicators. The highest scores were given to pieces with a balanced combination of modal variability and functional harmony (M = 9.8; SD = 0.6), and the difference between integrative and asymmetric synthesis models was statistically significant (t = 2.14; p < 0.05; d = 0.61). The analysis of the structural data showed that Western samples are characterized by the dominance of functional tonality and articulatory clarity (W = 0.83; W = 0.85). At the same time, the Eastern samples are characterized by microtonality and melismatic ornamentation (W = 0.80; W = 0.81). The obtained results demonstrate a moderate but stable relationship between the structural characteristics of vocal material and its perceptual evaluation. The proposed approach provides a formalized toolkit for the study of transcultural vocal hybridity. It can be used in further comparative musicological and pedagogical studies.